Analysis of the apical constriction using micro-computed tomography and anatomical sections - Filippo Citterio; Alberto Pellegatta; Claudio Luigi Citterio; Marcello Maddalone (Ariesdue, 2014)
Objectives: The aim of this study is to assess the morphology, the prevalence and the topography of the apical constriction (AC) through a tridimensional analysis and compare the results with the available data reported in the literature. Materials and methods: 15 teeth were selected. The teeth were intact and atraumatically extracted, without signs of radicular resorption or previous root canal treatments. Each tooth was scanned with the micro-computed tomography at a resolution of 9 μm. Through computer reconstruction the roots were made transparent, in order to reveal the endodontic anatomy; two calibrated examiners assessed the prevalence and the morphology of the AC on two different projections for each tooth. The AC was classified as present (single, multiple, tapered) or absent (flaring, parallel, apical delta). Inter-rater agreement was computed applying Cohen's kappa. The distance between the AC and the apical foramen was determined by means of a digital ruler. Results and conclusion: 52.6% of the observed ACs was ambiguous (present on one projection but not on the other one). Only 21.0% of the canals showed a tridimensional AC (present on both projections). Inter-rater agreement was very good (k = 0.839). The morphology, from greater to least, was flaring (25%), single (21.1%), parallel (21.1%), tapered (19.7%), apical delta (10.5%) and multiple (2.6%). Inter-rater agreement was again very good (kappa = 0.869). Root canal anatomy as described in the literature is more conceptual than real. The presence of AC appears to be an exception rather than a canon.